Numerical and experimental evaluation of adhesion properties of asphalt-aggregate interfaces using molecular dynamics simulation and atomic force microscopy. Issue 7 (3rd July 2022) - Cui, Bingyan; Gu, Xingyu; Wang, Hao; Hu, Dongliang
Abstract : This study evaluated the effects of aging and moisture on the adhesion properties of asphalt-aggregate interfaces. The work of adhesion obtained from molecular dynamics (MD) simulations and atomic force microscopy (AFM) tests were compared. The adhesive forces of asphalt before and after immersing in water were obtained by the peak force tapping quantitative nanomechanical (PFT-QNM) mode of AFM tests. Results showed that the average size of bee structures became larger after aging. The adhesive forces of the para-phase were the highest. A strong correlation was found between the adhesion properties obtained from MD simulations and AFM tests. The increase in asphaltene index could improve the adhesion, whereas the changes in molecular structures due to oxidative aging would weaken it. The balance of changes in them determined the overall adhesion properties. After immersing in water, the adhesion properties of aged asphalt were more susceptible to moisture damage.